IT-enabled Adaptive Open Innovation - Huber, Sebastian; Schott, Peter; Lederer, Matthias (ECIS 2015 Completed Research Papers, 2015)
Lacking efficiency and transparency regarding cross-company collaboration in the field of in-novation management often leads to cost intensive and unsuccessful products and services. This is due to the fact that traditional Innovation Management approaches fail in terms of coping with emerging requirements in Open Innovation projects, e.g. the vertical and horizontal inte-gration of strategic partners within and across the company’s value network. However, compa-nies are forced to maintain their competitive advantage through a constant and sustainable de-velopment of their product and service portfolio. In this context, knowledge workers play an im-portant role in the collaborative advancement of innovative product and service ideas. For that reason, knowledge workers need systematic support regarding both methodological and opera-tional challenges in the field of Open Innovation. The concept of Adaptive Case Management emerged from the necessity to support knowledge workers in unpredictable working environ-ments. Therefore, this contribution shows, both from a conceptual and technological point of view, how knowledge workers can be supported in cross-border innovation projects. The ap-proach is evaluated using an Adaptive Case Management software prototype and the findings on concept acceptance and software usability are presente
WiSo2-Import:2015-10-02:656